An Historical Overview: The Discovery of How NK Cells Can Kill Enemies, Recruit Defense Troops, and More - Vitale, Massimo; Cantoni, Claudia; Della Chiesa, Mariella; Ferlazzo, Guido; Carlomagno, Simona; Pende, Daniela; Falco, Michela; Pessino, Annamaria; Muccio, Letizia; De Maria, Andrea; Marcenaro, Emanuela; Moretta, Lorenzo; et al. (Frontiers in Immunology, 2019)
Natural killer (NK) cells were originally defined as effector lymphocytes of innate immunity characterized by the unique ability of killing tumor and virally infected cells without any prior priming and expansion of specific clones. The “missing-self” theory, proposed by Klas Karre, the seminal discovery of the first prototypic HLA class I-specific inhibitory receptors, and, later, of the Natural Cytotoxicity Receptors (NCRs) by Alessandro Moretta, provided the bases to understand the puzzling behavior of NK cells. Actually, those discoveries proved crucial also for many of the achievements that, along the years, have contributed to the modern view of these cells. Indeed, NK cells, besides killing susceptible targets, are now known to functionally interact with different immune cells, sense pathogens using TLR, adapt their responses to the local environment, and, even, mount a sort of immunological memory. In this review, we will specifically focus on the main activating NK receptors and on their crucial role in the ever-increasing number of functions assigned to NK cells and other innate lymphoid cells (ILCs).